The Fulfillment of Children with Disabilities Education Rights in West Kalimantan - Yenny AS; Henny Damaryanti; Klara Dawi (Proceedings of AICS - Social Sciences, 2018)
Central and Local Government had a duty to give rights for children with disabilities. The purpose of the study to find both the factor and obstacle in the lack of education rights children with disabilities in West Kalimantan. Through socio legal research method and qualitative approach, the study found that there was no accurate children with disabilities data. However, Family Communication  and Children with Disabilities Forum (Forum Komunikasi Keluarga dan Anak Cacat) noted there were totally 1.121 (28,02%) only children with disabilities who could access their education through Extraordinary School (Sekolah Luar Biasa) of the whole 4.001 children disabilities in 2010. The following factors affecting were the lack of inclusing school facilities, infrastructures and high education cost for children with disabilities, so parents and family were not able yet to access the education for their children.  The implication of the study show it needed concrete step such policy and Local Government commitment in providing free education access in school inclusing for children with disabilities in every district/city regions.Keywords:children, disabilities, education rights.